The Theology of Ibn Taymiyyah and the Rise of Salafi Ideology in Indonesia - Raihan Pradipta; gazali gazali (Academica: Journal of Multidisciplinary Studies, 2025)
This article explores the evolution of Ibn Taymiyyah’s theological thought and its influence on the rise of Salafi ideology in Indonesia. Ibn Taymiyyah is recognized as a prominent theologian who emphasized the purification of Islamic teachings by returning to the Qur’an and Sunnah. His concept of tawhid, Rububiyyah, Uluhiyyah, and Asma’ wa Sifat, became the fundamental basis for Salafi movements that reject rational interpretation and uphold the supremacy of revelation. This study employs a qualitative approach using library research and content analysis of Ibn Taymiyyah’s works as well as literature on Salafi ideology. The findings reveal that Salafi ideology has developed into several categories: Salafi Ilmi, which focuses on education and scholarly transmission; Salafi Manhaj, which emphasizes methodological approaches in da’wah; Salafi Jihadi, which advocates armed struggle; and Salafi Takfiri, which is characterized by extreme excommunication of others. The Islamic University of Imam Muhammad ibn Saud serves as a strategic institution in disseminating these ideas through education, religious outreach (da'wah), and its alumni network across various countries, including Indonesia. Thus, the connection between Ibn Taymiyyah, Salafism, and Imam Muhammad ibn Saud University reflects a strong ideological continuity in shaping contemporary religious practices focused on the purification of creed and worship.